A common sequence motif associated with recombination hot spots and genome instability in humans. - Myers, S; Freeman, C; Auton, A; Donnelly, P; McVean, G (2008)
In humans, most meiotic crossover events are clustered into short regions of the genome known as recombination hot spots. We have previously identified DNA motifs that are enriched in hot spots, particularly the 7-mer CCTCCCT. Here we use the increased hot-spot resolution afforded by the Phase 2 HapMap and novel search methods to identify an extended family of motifs based around the degenerate 13-mer CCNCCNTNNCCNC, which is critical in recruiting crossover events to at least 40% of all human hot spots and which operates on diverse genetic backgrounds in both sexes. Furthermore, these motifs are found in hypervariable minisatellites and are clustered in the breakpoint regions of both disease-causing nonallelic homologous recombination hot spots and common mitochondrial deletion hot spots, implicating the motif as a driver of genome instability.